Explicit robust multi-model predictive control - Falugi,P; Olaru,S; Dumur,D (2008)
The paper deals with robust predictive control based on a LMI approach. With respect to the well established case of linear models, with a global polytopic uncertainty, in the present approach the conservativeness reduction is assured by allowing different local descriptions of the uncertainty. The prediction model can thus be interpreted as a multi-model description of the plant to be controlled. The techniques is effective for a large class of nonlinear systems embedded into polytopic models. For the practical implementation the construction of suitable (explicit) descriptions of the control law are described upon concrete algorithms. © 2008 IEEE.